Perbandingan Stabilitas Dinding Penahan Tanah Tipe Bronjong dengan Tipe Kantilever di Kabupaten Probolinggo - Haryono, Muhammad Iqbal Yefa Imam; Solin, Dian Purnamawati; Farichah, Himatul (Universitas Batanghari Jambi, 2025)
Retaining walls (DPT) are essential structural elements in geotechnical engineering that function to withstand lateral earth pressure, especially in areas with elevation differences or slopes that are at risk of landslides. This study aims to analyze and compare the stability of two types of retaining walls: gabion retaining walls and cantilever retaining walls, based on safety factors against overturning, sliding, and bearing capacity. The study was conducted at a construction site in Probolinggo Regency using secondary data consisting of borehole soil investigation data and design drawings. Calculations of active and passive earth pressures, moments, and safety factors were performed manually using the Rankine method. The results show that the cantilever retaining wall has a higher overturning stability of 3.2, compared to 2.73 for the gabion wall. The cantilever wall also has a sliding stability of 2.76 and can be more optimally adapted to the soil's bearing capacity through a foundation design yielding a value of 7.95, compared to the gabion wall’s sliding stability of 2.07 and bearing capacity of 3.4. Therefore, the cantilever retaining wall is selected as an alternative to the existing gabion wall, as it outperforms in all safety factor assessments, including overturning, sliding, and bearing stability.